Antibody-Mediated Immunity against Tuberculosis: Implications for Vaccine Development - Achkar, Jacqueline M. (2013)
There is an urgent need for new and better vaccines against tuberculosis (TB). Current vaccine design strategies are generally focused on the enhancement of cell-mediated immunity. Antibody-based approaches are not being considered, mostly due to the paradigm that humoral immunity plays little role in the protection against intracellular pathogens. Here, we reappraise and update the increasing evidence for antibody-mediated immunity against Mycobacterium tuberculosis, discuss the complexity of antibody responses to mycobacteria, and address mechanism of protection. Based on these findings and discussions, we challenge the common belief that immunity against M. tuberculosis relies solely on cellular defense mechanisms, and posit that induction of antibody-mediated immunity should be included in TB vaccine development strategies.